A macroecological perspective for phenological research under climate change. Issue 5 (5th July 2017) - Doi, Hideyuki; Gordo, Oscar; Mori, Terutaka; Kubo, Mayumi T.
Abstract: Life cycles of animals and plants worldwide are shifting in response to recent climate change. Macroecology, which deals with biological patterns and processes at a large scale, is ideally suited to address this global phenomenon, thus providing a more general and generalizable understanding of the impacts of climate change on ecosystems. To date, a macroecological approach to examining phenological changes based on historical ground observations remains mostly unexplored, as the phenological studies have been conducted at local scales, while the recent new technologies, e.g., remote sensing, can extend phenological study to global scales. Because phenology is probably the most widely used bioindicator of climate change, thus allowing for studies at the macroscale. Some meta‐analyses have indeed employed broad‐scale, long‐term datasets to estimate overall shift rates in the timing of plant and animal phenological events. However, none has provided a convincing macroecological view of current phenological shifts, and few attempts have been made to make global‐scale predictions of phenological responses under future climatic scenarios. Understanding spatial variability and clines may be essential for comprehending phenological variations stemming from future climate change. Here, we discuss how ecological mechanisms discovered in macroecology may provide new insights for understanding spatial variation of sensitivity of phenology to climate change.